Productivity and economic growth in the European Union: Impact of investment in research and development - Andreja Nekrep; Sebastjan Strašek; Darja Boršič (Naše gospodarstvo / Our Economy, 2018)
This paper focuses on investment in research and development as a factor of labour productivity and economic growth. Our analysis confirms the link between expenditure for research and development (expressed in % of GDP) and labour productivity (expressed in the number of hours worked) based on selected data for EU Member States in the period 1995-2013. A causal link between variables of the concave parabola was confirmed, and the value of expenditure for research and development (2.85% of EU GDP) maximising productivity (per hour of work) was determined based on the examined data. In accordance with these findings, EU's target of reaching 3% of GDP spent on research and development to be achieved by 2020 seems in support of reaching maximum productivity in the EU.
Keywords: O31; O47; C23; 330; investment in research and development; productivity; economic growth; correlation; panel analysis